The formation of nurses in residency programs in public and private intensive care units - Iasmim Lima Aguiar; Lívia Magalhães Costa Castro; Anna Gabriella Carvalho Rangel; Larissa Chaves Pedreira; Norma Carapiá Fagundes
This qualitative study aimed to acknowledge the importance of practice in public and private institutions in the training of nurses in residency programs. Data were collected at two hospitals between February and March 2013, through interviews. From their analysis the following categories emerged: experience of graduate nurses in residency programs in ICUs of public and private institutions and potential for learning in public and private institutions regarding the training of nurses. Differences were detected in the work process and in the profile of patients between the public and private fields, and dissociation between caring and management functions carried out by residents was demonstrated. It was concluded that the development of practices in public and private institutions provides different and complementary experiences which prepare residents for management and care activities, improve management and technical assistance skills, encourages the exercise of in-service education and, by means of surveys, the search for solutions to problems that emerge from daily work.